Evaluation of Business Feasibility of Construction and Building Services Business at CV. Nirwatama - Dewi, Gusti Ayu Diah Arini; Iriani, Iriani (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
In developing a construction service business, it must consider various possibilities and developments in the future. Evaluation of business feasibility from various aspects is carried out in order to have clear goals and directions. CV. Nirwatama is a construction service industry company that belongs to the small class (K) category. Evaluation of business feasibility is carried out with two aspects, namely non-financial aspects and financial aspects. In the non-financial aspect, the CV. Nirwatama company can be said to be feasible enough to continue running in the next few years. While in the financial aspect of finance, the payback period (PP) value is obtained as much as 4 years 8 months 5 days < 5 years. Then at a net present value (NPV) of IDR. 14,114,466 and an internal rate of return (IRR) value of 14%> MARR = 12%. So it can be concluded that the construction services business of the CV. Nirwatama company is said to be very profitable and feasible to run or invest. One of the projects undertaken by CV. Nirwatama, namely the Light Rehabilitation of the Non-Rise Building of the Great Mosque, has significant problems regarding time delays in project work so that the contractor must coordinate again with the architect planner. To overcome time delays and minimize fines, this research uses the Critical Path Method (CPM). The result of the CPM method is that the optimal time duration for project work is 19 days so that the company is not subject to fines.